ASSESSING JOB SATISFACTION WITHIN THE SPORTS TEAMS OF IAŞI, ROMANIA - Oana RUSU (ALTIUS ACADEMY Foundation - Faculty of Physical Education and Sports, 2012)
Work is a part of our lives. We often spend a lot of the day working; job satisfaction - both at the personaland at the group or organization level - represents an important aspect of our professional activity. We aim to assessthe level of job satisfaction of the members of sports groups, by attempting to describe objectively the situations of thesports groups within the city of Iaşi (Romania), part of the first and second sports divisions. We have questioned 158athletes (55 female athletes and 103 male athletes playing basketball, football, handball, rugby, and volleyball). Therespondents answered to a standardized 32-item questionnaire; the items were grouped into four factors (pay andpromotion; management and interpersonal relations; organization and communication; general satisfaction). Thehomogeneity instrument was assessed for the entire scale, as well as independently for each factor. The lack ofvariance homogeneity made it impossible to get outcomes for the interaction of the independent variables such as theclub and the status. For the dimension pay and promotion, both the club type and the status of athletes exert influenceson the satisfaction of athletes. For the dimension management and interpersonal relations, the semi-professionalathletes are more satisfied compared to the professional athletes. The level of general satisfaction of the athletes withinthe teams studied is higher in the case of professional than in that of semi-professional athletes. The variable biologicgender does not influence the level of any factor of job satisfaction for the sports teams within the local communityspace.